1997
DOI: 10.1046/j.1365-2818.1997.2410797.x
|View full text |Cite
|
Sign up to set email alerts
|

Far‐field fluorescence microscopy with three‐dimensional resolution in the 100‐nm range

Abstract: SummaryWe report three-dimensional (3D) microscopy with nearly isotropic resolution in the l/5 ¹ l/10 range. Our approach combines 4Pi-confocal two-photon fluorescence microscopy with image restoration. The 3D resolution is demonstrated with densely clustered beads as well as with F-actin fibers in mouse fibroblast cells. A comparison with unrestored twophoton confocal images reveals a total reduction of the uncertainty volume up to a factor of 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 23 publications
1
71
0
1
Order By: Relevance
“…Phase artifacts leading to noteworthy misrepresentations of the objects can be ruled out. Nonlinear image restoration further increases the resolution by 50% (13), so that we applied nonlinear image processing to all 3D sets shown further in the paper. The final transverse resolution of Ϸ140 and Ϸ100 nm along the optic axis is not yet sufficient to discriminate single cristae; however, the 3D representation of the tubular structure of the mitochondria is fundamentally improved.…”
Section: Multifocal Multiphoton 4pimentioning
confidence: 99%
See 1 more Smart Citation
“…Phase artifacts leading to noteworthy misrepresentations of the objects can be ruled out. Nonlinear image restoration further increases the resolution by 50% (13), so that we applied nonlinear image processing to all 3D sets shown further in the paper. The final transverse resolution of Ϸ140 and Ϸ100 nm along the optic axis is not yet sufficient to discriminate single cristae; however, the 3D representation of the tubular structure of the mitochondria is fundamentally improved.…”
Section: Multifocal Multiphoton 4pimentioning
confidence: 99%
“…This concept is particularly powerful in connection with multiphoton excitation, because it substantially reduces undesired interference side lobes and provides a higher contrast of the interference pattern. Thus multiphoton 4Pi-confocal microscopy leads to a reliable axial resolution improvement (3,13) of the order of 90-150 nm in both aqueously mounted (14) and glycerol-mounted fixed cells (13). Unfortunately, relying on stage scanning, whereby the sample is scanned slowly through the focus of the lenses, 4Pi-confocal microscopy has been hampered by slow data acquisition.…”
mentioning
confidence: 99%
“…2 Two-photon techniques, which break the diffraction resolution limit, are based on point spread function engineering and must be mentioned when giving a general review of imaging techniques for biosciences. 4π microscopy, STED microscopy and triple-state depletion microscopy are just some of these methods, which have been especially developed in the group of Stefan Hell (Max Plank Institute, Goettingen, Germany) [23][24][25] . These techniques are particularly appropriate for optical imaging on the nanometer scale but are completely inadequate for measurements in (usually) thick biological samples.…”
Section: Fluorescence Imaging Techniquesmentioning
confidence: 99%
“…As the mounting medium of our specimens (glycerol) had a refractive index smaller than that of immersion oil and glass, n Ϸ 1.47 as opposed to n ϭ 1.51, the optical paths' lengths and hence the phase of the two beams changed during the axial translation of the sample. It has been shown that this phase change is a linear function of the scan and can be actively compensated by synchronously moving the piezo mirror with the axial movement of the sample (Egner et al, 1998;Hell et al, 1997). Therefore, in a largely uniform volume such as the cytoplasm of a fixed cell, the 4Pi PSF can be kept constant even in the presence of a significant refractive index mismatch between the mounting medium and the glass cover slip.…”
Section: Pi-confocal Microscopymentioning
confidence: 99%